Fiscal Policy and Financing of Water Resources Management Projects in Iraq: Challenges and Solutions - Abdulridha, Mustafa Mahdi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
Exacerbated by way of weather trade, population boom, and terrible monetary coverage, Iraq's water sources management is in huge hassle. Sustainable Financing Mechanisms: Fiscal policy is a chief source or device to offer long-term financing arrangements to finance infrastructure projects that preserve and distribute water. Government economic policy plays a crucial role in nearly each realizable thing of the financial system, while a brand new ecology, adapted to an increasingly scarce approach of obvious survival, might call for a holistic technique, which needs to be taken severely and need to, therefore, come to the fore in overcoming this kind of barriers to the financing of effective water resources management in Iraq. The objective of the studies is evaluate authorities expenditure, tax guidelines and the financial incentives that affect water handling projects The have a look at explores economic measures and their position in making sure sustainability of water sources and affords pointers for enhancing financial governance and aid productivity (Al-Ansari et al., 1970).